“War Is Old Men Talking and Young Men Dying:” The Story of Dennis Lee Klimpke - Cropsey, Garrett M. (My University, 2017)
This paper focuses on the letters sent and received by a solider fighting in Vietnam. Dennis Lee Klimpke, a 20-year-old from the small town of Colby, Wisconsin, reported for induction on August 7, 1967, at 1:45 pm. He was shipped out immediately thereafter to basic training at Fort Campbell, Kentucky. Five months later, Dennis found himself "humping the bush" and fighting to stay alive in the middle of the Vietnam jungle. In less than four months of enduring the hot and humid battles of the war, on April 15, 1968, he was killed in action. The 16 letters sent back and forth between Dennis and his mother and siblings are a powerful illustration of what it was like for the average infantryman during the Vietnam War. An incredible transformation takes place from his first letter to his last. He is fighting the Vietcong while also dealing with problems back home. This is a story of one man's experience in Vietnam, but relates to many, many more.
USGZE AS333
Keywords: Vietnam War, 1961-1975 -- Correspondence; Vietnam War, 1961-1975 -- Social aspects; Vietnam War, 1961-1975 -- Sources; Soldiers -- Wisconsin -- Colby; Vietnam War, 1961-1975 -- Veterans -- United States; Veterans -- United States; Vietnam War, 1961-1975 -- United States